P325 A propensity score-weighted comparison of vedolizumab and adalimumab in Crohn's disease: Real-life data from the Sicilian Network for inflammatory bowel disease (SN-IBD). (15th January 2020) - Macaluso, F S; Ventimiglia, M; Fries, W; Viola, A; Sitibondo, A; Cappello, M; Scrivo, B; Busacca, A; Privitera, A C; Camilleri, S; Garufi, S; Di Mitri, R; et al.
Abstract: Background: Currently, there are no randomised controlled trials focussing on direct comparisons between biologics in Crohn's disease (CD), while there is an unmet need to better understand and compare the effectiveness of these drugs. We performed a multicentre, real-life, comparison of the effectiveness of vedolizumab (VDZ) and adalimumab (ADA) in CD. Methods: Data of consecutive patients with CD treated with VDZ and ADA from January 2016 to April 2019 were extracted from the cohort of the Sicilian Network for Inflammatory Bowel Disease (SN-IBD). A propensity score analysis was performed using the Inverse Probability of Treatment Weighting (IPTW) method. The effectiveness was evaluated at 12 weeks, 52 weeks, and as treatment persistence at the end of follow-up. The clinical endpoints were steroid-free clinical remission (Harvey–Bradshaw Index < 5 without steroid use) and clinical response (reduction of the Harvey–Bradshaw Index ≥ 3 points with a concomitant decrease of steroid dosage compared with baseline). The sum of the two outcomes was defined as a clinical benefit. The achievement of endoscopic response (a reduction of Simple Endoscopic Score for CD ≥ 50% compared with baseline) or mucosal healing (Simple Endoscopic Score for CD ≤ 2) was assessed after at least 6 months of treatment. Results: A total of 585 treatments (VDZ: n = 277; ADA: n = 308) were included, with a median follow-up of 56.0 weeks (IQR 24.0–104.0). After 12 weeks, a clinical benefit was achieved in 64.3% patients treated with VDZ and in 83.1% patients treated with ADA ( p = 0.11 in propensity score analysis), while at 52 weeks a clinical benefit was observed in 54.0% patients treated with VDZ and in 69.1% patients treated with ADA ( p = 0.33 in propensity score analysis). The median treatment persistences for VDZ and ADA were 52 weeks and 64 weeks, respectively. Cox survival analysis weighted for IPTW showed no significant difference in the probability of treatment discontinuation between the two drugs (HR for VDZ=1.20; p = 0.34). Post-treatment endoscopic response and mucosal healing rates were similar between the two drugs (endoscopic response: 35.3% for VDZ and 25.5% for ADA, p = 0.15; mucosal healing: 31.8% for VDZ and 33.8% for ADA, p = 0.85). Conclusion: This is the first real-life study comparing VDZ and ADA in CD patients via propensity score-adjusted analysis. Even if crude rates of all clinical outcomes were higher for ADA compared with VDZ, such differences were not significant when patients' characteristics at baseline were weighted by propensity score.